2015
DOI: 10.4142/jvs.2015.16.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of strontium, barium, cadmium, copper, zinc, manganese, chromium, antimony, selenium, and lead in the liver and kidneys of dogs according to age, gender, and the occurrence of chronic kidney disease

Abstract: This study was conducted to measure the concentrations of strontium (Sr), barium (Ba), cadmium (Cd), copper (Cu), zinc (Zn), manganese (Mn), chromium (Cr), antimony (Sb), selenium (Se), and lead (Pb) in canine liver, renal cortex, and renal medulla, and the association of these concentrations with age, gender, and occurrence of chronic kidney disease (CKD). Tissues from 50 dogs were analyzed using inductively coupled plasma mass spectrometry. Cu, Zn, and Mn levels were highest in the liver followed by the rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
0
27
4
Order By: Relevance
“…The present study, similarly to the study by Paßlack et al [15], and contrary to the study by López-Alonso et al [22] found statistically significant differences in Se levels in the liver and kidneys of young and old dogs. There were also statistically significant differences in Se concentrations in the liver of young and old dogs from northwestern Poland, red and silver foxes from the same area [8,10], and raccoon dogs from southeastern Poland [24].…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…The present study, similarly to the study by Paßlack et al [15], and contrary to the study by López-Alonso et al [22] found statistically significant differences in Se levels in the liver and kidneys of young and old dogs. There were also statistically significant differences in Se concentrations in the liver of young and old dogs from northwestern Poland, red and silver foxes from the same area [8,10], and raccoon dogs from southeastern Poland [24].…”
Section: Discussioncontrasting
confidence: 57%
“…Much higher Se levels than in the present study were found by Paßlack et al [15] in dogs fed commercial feed.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations